COMPUTER MODELING OF THE SPATIAL DISTRIBUTION OF THE CRYSTALLIZING STEEL DENSITY IN THE SYSTEM «CASTING- DISCARD» - A. N. Chichko; S. G. Lihouzov; V. F. Sobolev; O. A. Sachek; T. V. Matyushinets; O. I. Chichko (Литьë и металлургия)
The modeling of the shrinkage processes in the steel casting with a head for the different modes of instant steel casting for isotropic heat dissipation with different initial temperature of the metal was held. The calculations of the statistical distribution of temperatures and densities for various moments of time in the crystallizing casting with a head and comparative analysis with the density distributions in the cast without a head for similar temperature conditions are made.